Height Simulation in a Virtual Reality CAVE System: Validity of Fear Responses and Effects of an Immersion Manipulation - Gromer, Daniel; Madeira, Octávia; Gast, Philipp; Nehfischer, Markus; Jost, Michael; Müller, Mathias; Mühlberger, Andreas; Pauli, Paul (Frontiers in Human Neuroscience, 2018)
Acrophobia is characterized by intense fear in height situations. Virtual reality (VR) can be used to trigger such phobic fear, and VR exposure therapy (VRET) has proven effective for treatment of phobias, although it remains important to further elucidate factors that modulate and mediate the fear responses triggered in VR. The present study assessed verbal and behavioral fear responses triggered by a height simulation in a 5-sided CAVE (Cave Automatic Virtual Environment) with visual and acoustic simulation and further investigated how fear responses are modulated by immersion, i.e. an additional wind simulation, and presence, i.e. the feeling to be present in the virtual environment. Results revealed a high validity for the CAVE virtual environment in provoking height related self-reported fear and avoidance behavior in accordance with a trait measure of acrophobic fear. Increasing immersion significantly increased fear responses in high height anxious participants, but did not affect presence. Nevertheless, presence was found to be an important predictor of fear responses. We conclude that a CAVE system can be used to elicit valid fear responses, which might be further enhanced by immersion manipulations independent from presence. These results may help to improve VRET efficacy and its transfer to real situations.